Preparation of high peel strength and high anti-aging epoxy adhesive that used for bonding aluminum alloy without surface treatment. Issue 16 (18th August 2019) - Wang, Zhiwei; Liu, Lijia; Li, Yonghe; Wang, Chao; Dong, Hongxing; Chen, Zeming; Zhang, Chunhong
Abstract: In the case of bonding of aluminum alloy, surface pretreatment have been widely adopted for adherends so as to achieve superior adhesive performance. However, the strict surface treatment of the aluminum alloy cannot be implemented without special equipment and the mechanical properties, corrosion resistance and aging resistance of the common adhesives cannot meet the demand without surface treatment. Here, acrylic oligomer modified by carboxyl terminated organosilicon and nano alumina were used to modify an epoxy formulation based on a classical DGEBA monomer to produce a high peel strength epoxy adhesive that can be used without surface pretreatment. The peel strength and the shear strength of the adhesive could reach 7.18 N/cm and 18.75 MPa, respectively, and could be well maintained under −70 °C and 100 °C. The novel adhesive also has good heat aging resistance, water resistance and artificial seawater resistance. SEM and XPS were used to investigate mechanism of aging resistance of modified adhesives without surface treatment.